Minat dan Bakat Mahasiswa Dakwah Pada Kegiatan Khithabah - Jujun Junaedi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2012)
Khithabah as part of sermons, including one method of propagation in the context of mass communication that preachers often do. Khithabah become a popular paradigm that the escort mission dynamics of mass media propaganda with all kedakwahannya effectiveness. Often khithabah conducted limited spread Islamic ideology which incidentally is the transfer of ideas with a bunch of speeches recreational bandage which in turn offers the essence of propaganda about itself. However, the insertions are not rare in any recreational activity khithabah a bargaining power for their own propaganda and a lover of excellence in the Islamic world that in fact describe the nature of grace for the whole of nature.